E-065 Medium-Term Clinical Outcome of Patients with Aneurysmal Subarachnoid Haemorrhage Treated Endovascularly within the Framework of a Multi-Disciplinary Neurovascular Team at a Tertiary Referral Medical Centre over a 45-Month Period. (14th July 2013) - Almandoz, J Delgado; Kadkhodayan, Y; Crandall, B; Scholz, J; Anderson, R; Lockhart, K; Mowbray-Donahue, T; Uittenbogaard, K; Dyste, G; Fease, J; Tubman, D
Abstract : Purpose: To determine the medium-term clinical outcome in a cohort of patients presenting with aneurysmal subarachnoid haemorrhage (SAH) treated endovascularly within the framework of a multi-disciplinary neurovascular team at a tertiary referral medical centre over a 45-month period. Methods: We conducted a retrospective review of all patients who presented to our institution with aneurysmal SAH and underwent endovascular treatment of the ruptured aneurysm within the framework of a multi-disciplinary neurovascular team from January 1st, 2009, until September 30th, 2012. Baseline clinical characteristics, surgical and endovascular interventions performed and discharge disposition were recorded. Clinical outcome at the time of last follow-up was assessed with the modified Rankin Scale (mRS). A good clinical outcome was defined as an mRS 0–2. Results: One-hundred and twenty-four patients presented with aneurysmal SAH and underwent endovascular treatment of the ruptured aneurysm at our institution during the study period. Eighty-seven patients were female (70.2%) and 37 male (29.8%), with a mean age of 56.2 years (median 57 years, range 22–91 years). Sixty-eight patients required placement of an external ventricular drain (54.8%), 28 placement of a ventriculoperitoneal shunt (22.6%), and 6 a decompressive craniectomy (4.8%). Twenty-six patients required endovascular treatment of symptomatic cerebral vasospasm (21%), 85% of which were treated with balloon-angioplasty of the affected vessel (s) with or without an intra-arterial nicardipine infusion, and 15% were treated with an intra-arterial nicardipine infusion only. Mean Neuro-ICU length of stay was 14.3 days (median 14.5 days, range 1–39 days). Mean hospital length of stay was 19 days (median 18 days, range 1–39 days). Discharge disposition was home in 62 patients (50%), a rehabilitation facility in 39 patients (31.5%), a skilled nursing facility in 12 patients (9.7%), and 11 patients did not survive the hospitalisation (8.9%). Eight patients were lost to follow-up (6.5%). Mean time to last clinical follow-up for the 105 survivors with follow-up was 14.6 months (median 9.6 months, range 3.7–48 months). Overall, a good clinical outcome at the time of last clinical follow-up was observed in 83 patients (71.6%). The table summarises the clinical outcome at the time of last clinical follow-up according to admission Hunt-Hess scale in our patient cohort. Conclusion: The majority (72%) of patients presenting with aneurysmal SAH who underwent endovascular treatment of the ruptured aneurysm within the framework of a multi-disciplinary neurovascular team at our institution demonstrated a good clinical outcome at the time of last clinical follow-up, including 41% of patients with an admission Hunt-Hess scale 4–5. Clinical Outcome at the Time of Last Clinical Follow-up in Patients with Aneurysmal SAH Disclosures: J. Delgado Almandoz: 2; C; Covidien/ev3. Y. Kadkhodayan: None. B. Crandall: 2; C; Covidien/ev3. J. Scholz: None. R. Anderson: None. K. Lockhart: None. T. Mowbray-Donahue: None. K. Uittenbogaard: None. G. Dyste: None. J. Fease: None. D. Tubman: 2; C; Covidien/ev3, MicroVention.